New directions in the historiography of the administration of the Bloody Code - Walliss, John (History compass, 2018)
In this article, I will review the recent historiography of the administration of the so-called Bloody Code of the long eighteenth century. The 1970s and 1980s witnessed a debate among Marxist historians and others over the extent to which the Bloody Code operated as a tool of the ruling elite to protect property interests. In recent years, however, several historians have begun to explore a different series of questions in regard to the Bloody Code. One theme that unites the current work is an emphasis on the variability of the Bloody Code. In the article, I discuss three areas of variability highlighted by this work: time, geography, and judicial decision-making.